DESIGNING AND SCREENING OF POTENT INHIBITOR AGAINST INHA REDUCTASE OF MYCOBACTERIUM TUBERCULOSIS: A COMPUTATIONAL APPROACH - Joylaxmi Devi, Urikhimbam; Chetia, Pankaj; Anita Devi, Thokckom; Choudhury, Manabendra Dutta (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives: In this study, we attempt to design potent inhibitor specifically targeting the Mycobacterium tuberculosis enoyl-acyl carrier protein reductase. Methods: In silico docking studies were performed, using FlexX and Autodock Vina with ligand1 (library compound) and known inhibitors against enoyl acyl carrier protein reductase of Mycobacterium tuberculosis i.e., drug target. Ten proven inhibitors of InhA were selected from literature with their IC50 value and were correlated using EasyQSAR to generate QSAR model. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Results and Discussions: By a two-step screening method, we identified a library compound expected to have high binding affinity to the enoyl acyl carrier protein reductase. Molecular docking with library compound showed good docking score better than known inhibitors. Drug like properties of these ligand1 were calculated by ADME/Tox calculations. The QSAR analysis of all standard compounds showed significant correlation with R square is 99.29 %. Conclusion: We therefore, propose that (2-((3,5-dimethoxyphenyl)(hydroxy)carbamoyl)-5-methylphenyl)(7-oxo-4-thia-1-azabicyclo[3.2.0]heptan-3-yl)azinic acid is presenting better bioactivity against InhA target. Thus, this library compound as a potent InhA inhibitor and may be used in designing new anti-tubercular therapy. Â Keywords: Enoyl-acyl carrier protein reductase (InhA), ADME/Tox, Mycobacterium tuberculosis, Docking .